Adam Smith, Settler Colonialism, and Cosmopolitan Overstretch - INCE, Onur Ulas (Institutional Knowledge at Singapore Management University, 2017)
Adam Smith has recently been celebrated as a precocious theorist of commercialcosmopolitanism who decried the injustice of imperial conquest and extraction. This paperfocuses on Smith’s endorsement of settler colonialism in North America and argues thatSmith’s newfound cosmopolitanism is overstretched. Smith welcomed settler colonies as theembodiment of the “natural progress of opulence” and spared them from his invective againstother imperial practices like chattel slavery and trade monopolies. Smith’s embrace of settlercolonies, however, involved him in an ideological conundrum insofar as the prosperity ofoverseas settlements rested on imperial expansion and seizure of land from Native Americans.I contend that Smith muffled this disturbing link through a number of rhetorical strategies,evoking a vision of colonization without imperialism. Smith’s favorable treatment of settlercolonialism, I conclude, belongs to a longer genealogy of representing capitalism as anessentially liberal economic system in the face of its decidedly illiberal history. Investigatingthis genealogy necessitates breaking with the currently dominant conventions of studying thehistory of political thought and placing intellectual history in conversation with social theoryand political economy.